Extensive Philosophical Agreement and Progress. (January 2017) - Frances, Bryan
Abstract: This article argues, first, that there is plenty of agreement among philosophers on philosophically substantive claims, which fall into three categories: reasons for or against certain views, elementary truths regarding fundamental notions, and highly conditionalized claims. This agreement suggests that there is important philosophical progress. It then argues that although it's easy to list several potential kinds of philosophical progress, it is much harder to determine whether the potential is actual. Then the article attempts to articulate the truth that the deniers of philosophical progress are latching on to. Finally, it comments on the significance of the agreement and (potential) progress.